The disclosure of environmental conservation costs and its relation to eco-efficiency: Evidence from Japan. Issue 1 (6th March 2017) - Yook, Keun-Hyo; Song, Hakjoon; Patten, Dennis M.; Kim, Il-Woon
Abstract : Purpose: This paper aims to examine whether the amount of costs disclosed as relating to environmental controls is associated with environmental performance in terms of carbon-based eco-efficiency, and whether any relation supports voluntary disclosure theory or legitimacy theory arguments. Further, this paper attempts to determine whether the relations differ across the initial Kyoto Protocol period. Design/methodology/approach: In this study, the focus was on Japanese firms over the period from 2002 to 2012. Disclosed environmental control costs (capital expenditures and operating costs) were identified and eco-efficiency measures based on carbon emissions were calculated. Relations were tested for using regression models controlling for other potential impact factors. Findings: This study's results indicate a negative relation between disclosed levels of environmental control costs and eco-efficiency performance measures, and, for two of our three eco-efficiency metrics, this is more pronounced over the Kyoto Protocol period. Research limitations/implications: These results support a legitimacy theory (as opposed to voluntary disclosure theory) explanation for the relation between the levels of disclosed environmental control costs and carbon-based eco-efficiency. Originality/value: This study is the first to explore how flexibility in cost classification may be used by companies to foster a disclosure strategy.